Correction: Thiophene derivatives as corrosion inhibitors for 2024-T3 aluminum alloy in hydrochloric acid medium. Issue 24 (18th May 2022) - Arrousse, N.; Fernine, Y.; Al-Zaqri, Nabil; Boshaala, Ahmed; Ech-chihbi, E.; Salim, R.; El Hajjaji, F.; Alami, Anouar; Touhami, M. Ebn; Taleb, M.
Abstract : Correction for 'Thiophene derivatives as corrosion inhibitors for 2024-T3 aluminum alloy in hydrochloric acid medium' by N. Arrousse et al., RSC Adv., 2022, 12, 10321–10335, ; https://doi.org/10.1039/D2RA00185C .